2018
DOI: 10.1007/s00464-018-6288-8
|View full text |Cite
|
Sign up to set email alerts
|

Nodal upstaging evaluation in NSCLC patients treated by robotic lobectomy

Abstract: Robotic lobectomy for clinical N0-N1 NSCLC appears to be equivalent to thoracotomy in terms of efficacy of lymph node dissection and nodal upstaging. Given that the nodal upstaging is a surrogate of quality of surgery, we can consider robotic lobectomy an appropriate procedure which ensures similar result to the open approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“….34 in open group. In this study, the percentage of nodal upstaging in the two groups was similar, 20.8% by robotic surgery and 17.9% by open approach, confirming that lymphadenectomy by robotic approach can be precise, equalling open surgery [14] . Studies about oncologic outcomes after lung resection have confirmed the suitability in terms of oncologic radicality of resection of the robotic surgery for NSCLC treatment.…”
Section: Nodal Upstaging Evaluation In Robotic Surgery For Lung Cancersupporting
confidence: 67%
See 1 more Smart Citation
“….34 in open group. In this study, the percentage of nodal upstaging in the two groups was similar, 20.8% by robotic surgery and 17.9% by open approach, confirming that lymphadenectomy by robotic approach can be precise, equalling open surgery [14] . Studies about oncologic outcomes after lung resection have confirmed the suitability in terms of oncologic radicality of resection of the robotic surgery for NSCLC treatment.…”
Section: Nodal Upstaging Evaluation In Robotic Surgery For Lung Cancersupporting
confidence: 67%
“…Zirafa et al . [14] Thoracotomy is observed in about one-third of the patients after surgery. Rocha described a N2 upstaging in 8.3% of patients with preoperative negative nodes, investigated by mediastinoscopy [7] .…”
Section: Nodal Upstaging In Nsclcmentioning
confidence: 99%
“…The five-year overall survival was not different between the two groups (48.6% and 48.7%, respectively, P = 0.76). With RATS, the rate of nodal upstaging was not different compared to open surgery, and higher than with VATS [20,21] .…”
Section: Lymph Node Dissection and Nodal Upstaging By Rats Vats Andmentioning
confidence: 74%
“…Length of hospital stay RR 0.77 (95%CI 0.54-1.09) P = 0.14 Shorter in RATS group P < 0.05 Table 1. Main reports concerning short-term outcomes after lobectomy performed by thoracotomy or a minimally invasive approach as VATS or RATS for a NSCLC in studies used for this article principles as anatomical dissection and allows better lymph node dissection [20,21] . The main limitations for the wide deployment of RATS are the higher cost of the procedure compared to VATS [22] and logistical issues.…”
Section: Complication Ratementioning
confidence: 99%
See 1 more Smart Citation